Distinct regions of c-Mpl cytoplasmic domain are coupled to the JAK-STAT signal transduction pathway and Shc phosphorylation. - Gurney, A L (1995)
c-Mpl, a member of the hematopoietic cytokine receptor family, is the receptor for thrombopoietin. To investigate signal transduction by c-Mpl, a chimeric receptor, composed of the extracellular domain of human growth hormone receptor and the intracellular domain of c-Mpl, was introduced into the interleukin 3-dependent cell line Ba/F3. In response to growth hormone, this chimeric receptor induced growth in the absence of interleukin 3. Deletion analysis of the 123-amino acid intracellular domain indicated that the elements responsible for this effect are present within the 63 amino acids proximal to the transmembrane domain. Mutation of the recently described box 1 motif abrogated the proliferative response. Tyrosine phosphorylation of the tyrosine kinase JAK-2 and activation of STAT proteins were dependent on box 1 and sequences within 63 amino acids of the plasma membrane. STAT proteins activated by thrombopoietin in a megakaryocytic cell line were purified and shown to be STAT1 and STAT3. A separate region located at the C terminus of the c-Mpl intracellular domain was found to be required for induction of Shc phosphorylation and c-fos mRNA accumulation, suggesting involvement of the Ras signal transduction pathway. Thus, at least two distinct regions are involved in signal transduction by the c-Mpl.